Get strong to fight childhood cancer - an exercise intervention for children and adolescents undergoing anti-cancer treatment (FORTEe): rationale and design of a randomized controlled exercise trial - Neu, Marie Astrid; Dreismickenbecker, Elias; Lanfranconi, Francesca; Stössel, Sandra; Balduzzi, Adriana; Wright, Peter; Windsor, Stan; Wiskemann, Joachim; El-Rajab, Inaam; Lucia, Alejandro; Fiuza-Luces, Carmen; Mongondry, Rodolf; et al. (BMC cancer, 2025)
Despite substantial advances in treatment, children and adolescents with cancer continue to face high morbidity and health issues, including cancer-related fatigue, treatment-related complications, and physical inactivity. Integrating exercise into pediatric oncology care has emerged as a promising approach to mitigate these burdens during cancer treatment. While preliminary data support its potential to reduce treatment-related side effects and enhance quality of life, robust evidence -especially from large, multicenter trials- remains limited.